Komunikasi Ekonomi Pemerintah Daerah Dalam Sosialisasi Program Pemberdayaan Ekonomi Rakyat Di Kabupaten Bima - Muhsinin .; Yaumal Asri Adi Hutasuhut (CV. ITTC INDONESIA, 2025)
This study aims to analyze the economic communication strategies employed by the Bima Regency Government in promoting its community economic empowerment program. The primary focus is on how communication approaches are used to convey information, build participation, and encourage economic change among lower-income communities through empowerment programs. The research method used is a descriptive qualitative approach using interviews, observation, and documentation studies. The results indicate that the success of the empowerment program is highly dependent on the participatory communication model and local approach used by the local government.